Improvement of Congo Red Photodegradation Performance Through Zn/Al-TiO2 and Zn/Al-ZnO Preparation - Nova Yuliasari; Amri; Risfidian Mohadi; Elfita Elfita; Aldes Lesbani (Science and Technology Indonesia, 2022)
Layered double hydroxide (LDH) is an anionic clay material known to be effective as a catalyst for the photodegradation of dye organic pollutants. Zn/Al LDH was synthesized by coprecipitation then impregnated with metal oxides and calcined at 300oC to form Zn/Al-TiO2 and Zn/Al-ZnO as photodegradation catalysts of congo red (CR). The characterization of the catalysts after preparation using SEM and UV-DRS while the catalyst that have been used in 5 regeneration cycles was characterized by XRD and FTIR. Photodegradation of CR was carried out by optimizing pH, catalyst weight, and time radiation. Zn/Al LDH which was modified into Zn/Al-TiO2 and ZnAl-ZnO had a better degradation percentage, rate constant, and stability than Zn/Al LDH pristine structure. Zn/Al LDH, Zn/Al TiO2 and Zn/Al-ZnO catalyzed CR photodegradation for 120 minutes with percent degradation 68.39%, 81.24% and 71.09%, respectively.